PENGEMBANGAN MEDIA BILANGAN INTERAKTIF BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN OPERASI HITUNG DASAR PADA SISWA SLOW LEARNER - Dian Agestiningsih; Sujarwanto; Murtadlo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
His study aims to develop learning media in the form of interactive number cards based on Android that are specifically designed to improve basic arithmetic skills in slow learner students. Slow learner students require a different learning approach, especially in terms of visualization and interactivity, in order to understand basic mathematical concepts more effectively. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the trial consisted of slow learner students at the elementary school level of SDN Bulu 02, grade 3. The results of validation by material experts, media experts, and experts showed that the media developed were feasible and effective for use in learning. In addition, the evaluation results showed an increase in students' basic arithmetic skills after using this interactive media. Thus, this Android-based interactive number card media can be an innovative and enjoyable learning alternative for slow learner students in understanding basic arithmetic concepts.